Assessment of production efficiency by optimizing operational efficiency of fish processing in General Santos City - Mernilo, Emmanuel S. Jr.; Puso, Mark Ndsy L. (2019)
As an archipelagic country, fisheries and fish processing plants are two very important industries in the Philippines, as we are mostly surrounded by water. About 30 percent of the fish catch is processed into cured, canned, or frozen products. These industries are an important part of the agriculture sector of the Philippines. Efficiency is an essential part of these industries as it leads to more production of fish supply and products. This study is focused in identifying the production efficiency of these fish processing plants by studying the technical and operational efficiency. This study uses the Data Envelopment Analysis to analyze the data gathered from the three fish processing plants; General Tuna Corporation Plant (GTC), Local Tuna Corporation Plant (LTO), and the Bangus Plant. The space efficiency and requirements were analyzed through field observation and the floor plan given by the plants. The results show that the layout and flow of the floor plan are in sequence in respect to the operations. This study also shows the optimum space needed to maximize the output of each process, and each space needed for the equipment and the workers inside the workplace.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2019